Pattern of seed longevity during storage of lentil (Lens culinaris) cultivars - PARIHAR, ASHOK KUMAR; LAMICHANEY, AMRIT; SINGH, ANIL KUMAR; KATIYAR, PARDIP KUMAR; KUMAR, JITENDRA (The Indian Journal of Agricultural Sciences, 2023)
In the present study, the viability of 36 high yielding lentil cultivars were tested at an interval of 0 (before storage), 1, 2, 3 and 4 years of storage. In all the tested varieties, themean viability was 85, 94, 94, 93 and 50% when stored for 0, 1, 2, 3 and 4 years, respectively. Lentil being an orthodox seed can be stored well up to three years maintaining viability above the minimum requirement (75%) as perIndian Minimum Seed Certification Standards (IMSCS). Therefore, it is recommended to store the seeds of these varieties up to three years, except for VL 507, under ambient conditions. Notably, the seeds of nine varieties namely IPL 406, PL 639, Asha, PL 77-12, Ranjan, NDL 1, VL 103, WBL 77 and KLS 218 could be stored for more than 4 years. These varieties are identified with better storage ability andcould be embraced as donors in lentil breeding program for developing cultivars with better storage efficiency.